Legal Assistance Treaties in the Light of War and Expansion : Process, Motives and Protagonists of the German-Hungarian Legal Assistance Negotiations 1939–1942 - Hamann, Gerrit (Díké - Journal of Dezső Márkus Research Group for Comparative Legal History, 2025)
Cross-border legal assistance is an important indicator of close interstate relations. Remarkably, in the first years of the Second World War, a noticeable intensification of legal assistance between National Socialist Germany and the Kingdom of Hungary occurred. The reason for this was the common border that came into being with the ‘Anschluss’ of Austria. But the expansion of the legal assistance system was also due to the National Socialist expansion and hegemonic ambitions in Eastern Europe. Between 1939 and 1942, more than ten bilateral legal assistance treaties were negotiated. On the German side, notorious Nazi lawyers such as the later State Summaries 613 Secretary in the Federal Chancellor’s Office Hans Globke and the war criminal Max Merten were involved.